2022
DOI: 10.3390/ijerph191610050
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Avascular Necrosis Following the Stabilization of Femoral Neck Fractures: A Systematic Review and Meta-Analysis

Abstract: Background: Avascular necrosis (AVN) of the femoral head often requires surgical treatment and is often associated with femoral neck fractures. We conducted a systematic review and meta-analysis of recent research on the risk of AVN following the stabilization of fractured femoral neck with implants in PubMed. We assessed the effect of age on AVN incidence among patients aged > 50 and younger, depending on fracture type, Garden stage, Pouwels degree, Delbet stage, and age category. We followed PRISMA guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
(187 reference statements)
0
7
0
Order By: Relevance
“…Furthermore femoral neck fractures are highly susceptible to femoral head necrosis following surgery. Indeed, one study reported that the rate of femoral head necrosis after hollow screw fixation of femoral neck fractures could reach 20.7%, and even for nondisplaced fractures, the rate was 4.7%[ 28 ]. As a result, femoral neck fractures are commonly termed "unresolved fractures"[ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore femoral neck fractures are highly susceptible to femoral head necrosis following surgery. Indeed, one study reported that the rate of femoral head necrosis after hollow screw fixation of femoral neck fractures could reach 20.7%, and even for nondisplaced fractures, the rate was 4.7%[ 28 ]. As a result, femoral neck fractures are commonly termed "unresolved fractures"[ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…While osteonecrosis most frequently affects the femur, it can occur in various bones throughout the body. Osteonecrosis can be linked to a range of factors including the use of certain medications, traumatic injuries, excessive alcohol and narcotic consumption, or exposure to radiation [1][2][3]. Osteonecrosis of the jaw (ONJ), a specific form of osteonecrosis, greatly impacts the patient's quality of life and contributes to a notable mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In young adults, most femoral neck fractures are vertically unstable shear fractures (Pauwels type III femoral neck fracture), with a high incidence of postoperative femoral head ischemia and necrosis. 4 Anatomic reduction and stable internal fixation are among the principles for treating these fractures. 5 Stable fixation of fractures requires a reliable internal fixation device.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of femoral neck fracture, as an intracapsular fracture, has been increasing annually, particularly in young people 1–3 . In young adults, most femoral neck fractures are vertically unstable shear fractures (Pauwels type III femoral neck fracture), with a high incidence of postoperative femoral head ischemia and necrosis 4 . Anatomic reduction and stable internal fixation are among the principles for treating these fractures 5 …”
Section: Introductionmentioning
confidence: 99%